Tunable Phase Distribution of Liquid Metamaterial. Issue 2 (16th December 2021) - Lin, Jie; Lin, Peng; Lin, Yu-Sheng
Abstract : A tunable liquid metamaterial (TLM) is proposed and demonstrated to possess phase tunability. TLM is composed of SiO2 nanopillars encapsulated with silicone oil. The phase of incident wavelength of 660 nm can be tuned 2 π by elevating the height of SiO2 nanopillars to 1.65 μm. TLM shows high transmission intensity of 0.9. The phase manipulation is based on the liquid morphology, which is different from that by temperature and electrical methods. Herein, a TLM design is proposed to exhibit an actively tunable phase metamaterial and promote its application prospect. It provides the potential possibility of holography with high transmission intensity and shows actively tunable transmission phase to realize the tunable deflection angle, variable image, and varifocal metalens applications. This TLM design, an innovative idea for one kind of liquid metamaterial, is desirable to bring more possibilities to the tunable phase metamaterial. The adoptable electromagnetic spectrum of this design can also extend to the entire electromagnetic spectrum, such as microwave, terahertz (THz), infrared (IR), etc. The proposed TLM design provides an effective approach in tunable optoelectronics applications and a new direction for the future 3D stereoimaging and holographic projection applications. Abstract : A tunable liquid metamaterial (TLM) is proposed and demonstrated to possess phase tunability. TLM provides the potential possibility of holography with high transmission intensity and shows actively tunable transmission phase to realize the tunable deflection angle, variable image, and varifocal metalens applications. It is a new direction for future 3D stereoimaging and holographic projection applications.